Estrategias neurodidácticas para promover el desarrollo de la lectoescritura en los estudiantes del segundo grado de la Unidad Educativa Fiscomisional Educare, 2022-2023 - Quizhpe Montaño, Yoselin Nathalia (2023)
The present work of curricular integration had the objective of implementing neuro didactics strategies to promote the development of reading and writing in second grade students of the Unidad Educativa Fiscomisional Educare; it was a quantitative, descriptive, quasi-experimental, cross-sectional study. The Reading and Writing Analysis Test (TALE) was applied to a sample of 6 students. The results found in the pre-test in letter reading, 83% of the students made 26 or more errors, placing them in the lower level, and 17% made 13 to 25 errors, reaching the medium level; in spelling-copying, 67% made 18 or more errors, placing them in the lower level, and 33% made 9 to 17 errors, reaching the medium level; Following these results, a guide of neuro didactics strategies was implemented, structured by 7 workshops made up of a total of 20 activities that had the purpose of stimulating phonological and graphomotor awareness skills. After the application of the guide, the results of the post-test indicate that in reading, 67% of students are at the medium level, making between 13 to 25 mistakes and the remaining 33% remain at the lower level, while in writing, 50% reach the medium level, making between 9 to 17 errors and the remaining 50% remain at the lower level. It is concluded that in the pre-test the majority of students in reading and writing are in the lower level, which exceeds the number of errors as expected for their level of schooling, and after the intervention they decreased the number of errors reaching the medium level, which shows that the neuro didactics strategies promote the development of reading and writing in the students.